Synthesis and Properties of Enkephalin Oligonucleotide Conjugates - Ma1, Li; Zhu1, Han-Jing; Yao1, Cheng-Cheng; Lu1, Kui (Asian Journal of Chemistry, 2014)
Peptide-oligonucleotide conjugates (POCs) is a kind of potential gene therapy drugs. It has several applications, including improving antisense agents for interfering with the RNA function and targeting disease-causing mRNA within cells. In this paper, an efficient synthesis of six enkephalin-oligonucleotide conjugates had been accomplished by azide-alkyne cycloaddition, in which the oligonucleotide and peptides were directly appended by azide and alkyne groups. Meanwhile, the hydrolytic stability of enkephalin-oligonucleotide conjugates was studied by reversed phase HPLC and the interaction of the products with pUC18 DNA also conducted by agarose gel electrophoresis. The results obtained showed that the triazole linkage is much more stable in slightly acidic environment than in slightly alkaline, the interaction between enkephalin-oligonucleotide conjugates and pUC18DNA is stronger than that between enkephalin and pUC18 DNA.